Effect of paraquat-induced oxidative stress on gene expression and aging of the filamentous ascomycete Podospora anserina - Matthias Wiemer; Heinz D. Osiewacz (Microbial Cell)
Aging of biological systems is influenced by various factors, conditions and processes. Among others, processes allowing organisms to deal with various types of stress are of key importance. In particular, oxidative stress as the result of the generation of reactive oxygen species (ROS) at the mitochondrial respiratory chain and the accumulation of ROS-induced molecular damage has been strongly linked to aging. Here we view the impact of ROS from a different angle: their role in the control of gene expression. We report a genome-wide transcriptome analysis of the fungal aging model Podospora anserina grown on medium containing paraquat (PQ). This treatment leads to an increased cellular generation and release of H2O2, a reduced growth rate, and a decrease in lifespan. The combined challenge by PQ and copper has a synergistic negative effect on growth and lifespan. The data from the transcriptome analysis of the wild type cultivated under PQ-stress and their comparison to those of a longitudinal aging study as well as of a copper-uptake longevity mutant of P. anserina revealed that PQ-stress leads to the up-regulation of transcripts coding for components involved in mitochondrial remodeling. PQ also affects the expression of copper-regulated genes suggesting an increase of cytoplasmic copper levels as it has been demonstrated earlier to occur during aging of P. anserina and during senescence of human fibroblasts. This effect may result from the induction of the mitochondrial permeability transition pore via PQ-induced ROS, leading to programmed cell death as part of an evolutionary conserved mechanism involved in biological aging and lifespan control.